Neighborhood perceptions and hypertension among low-income black women: a qualitative study. (December 2016) - Al-Bayan, Maliyhah; Islam, Nadia; Edwards, Shawneaqua; Duncan, Dustin
Abstract Background The majority of studies examining the role of neighborhoods and hypertension-related outcomes have been quantitative in nature and very few studies have examined specific disadvantaged populations, including low-income housing residents. The objective of this study was to use qualitative interviews to explore low-income Black women's perceptions of their neighborhoods and to understand how those perceptions may affect their health, especially as it relates to blood pressure. Methods Seventeen Black female participants, living in public housing communities in New York City, completed one semi-structured, audiotaped interview in July of 2014. All interviews were transcribed, coded, and analyzed for emerging themes using N'Vivo 10 software. Results Three major themes emerged: (1) social connectedness, (2) stress factors, and (3) availability of food options. For example, factors that caused stress varied throughout the study population. Sources of stress included family members, employment, and uncleanliness within the neighborhood. Many participants attributed their stress to personal issues, such as lack of employment and relationships. In addition, the general consensus among many participants was that there should be a greater density of healthy food options in their neighborhoods. Some believed that the pricing of fresh foods in the neighborhoods should better reflect the financial status of the residents in the community. Conclusions Various neighborhood influences, including neighborhood disorder and lack of healthy food options, are factors that appear to increase Black women's risk of developing high blood pressure. Implications of this research include the need to develop interventions that promote good neighborhood infrastructure (e.g. healthy food stores to encourage good nutrition habits and well-lit walking paths to encourage daily exercise), in addition to interventions that increase hypertension awareness in low-income neighborhoods.